Progressive compression and transmission of PointTexture images - Song, In-Wook; Kim, Chang-Su; Lee, Sang-Uk (Journal of visual communication and image representation, 2006)
A progressive compression and transmission algorithm for PointTexture 3-D images is proposed in this work. The proposed algorithm represents a PointTexture image hierarchically using an octree. The geometry information in octree nodes is encoded by the predictive partial matching (PPM) method, while the color information is encoded using the discrete cosine transform (DCT). The encoder achieves the progressive transmission of the 3-D image by transmitting the octree nodes in a top-down manner. We develop two transmission schemes, based on the rate–distortion (R–D) optimization and the view-dependent optimization respectively, to maximize the image quality subject to a given bit budget. Extensive simulation results demonstrate that the proposed algorithm is an efficient method for progressive transmission of 3-D data.